Muscle-tendon-related pain in 100 patients with hip dysplasia: prevalence and associations with self-reported hip disability and muscle strength. Issue 1 (17th November 2017) - Jacobsen, Julie Sandell; Hölmich, Per; Thorborg, Kristian; Bolvig, Lars; Jakobsen, Stig Storgaard; Søballe, Kjeld; Mechlenburg, Inger
ABSTRACT: The primary aim was to identify muscle-tendon-related pain in 100 patients with hip dysplasia. The secondary aim was to test whether muscle-tendon-related pain is associated with self-reported hip disability and muscle strength in patient with hip dysplasia. One hundred patients (17 men) with a mean age of 29 years (SD 9) were included. Clinical entity approach was carried out to identify muscle-tendon-related pain. Associations between muscle-tendon-related pain and self-reported hip disability and muscle strength were tested with multiple regression analysis, including adjustments for age and gender. Self-reported hip disability was recorded with the Copenhagen Hip and Groin Outcome Score (HAGOS), and muscle strength was assessed with a handheld dynamometer. Iliopsoas- and abductor-related pain were most prevalent with prevalences of 56% (CI 46; 66) and 42% (CI 32; 52), respectively. Adductor-, hamstrings- and rectus abdominis-related pain were less common. There was a significant inverse linear association between muscle-tendon-related pain and self-reported hip disability ranging from −3.35 to − 7.51 HAGOS points in the adjusted analysis ( P < 0.05). Besides the association between muscle-tendon-related pain and hip extension a significant inverse linear association between muscle-tendon-related pain and muscle strength was found ranging from −0.11 to − 0.12 Nm/kg in the adjusted analysis ( P < 0.05). Muscle-tendon-related pain exists in about half of patients with hip dysplasia with a high prevalence of muscle-tendon-related pain in the iliopsoas and the hip abductors and affects patients' self-reported hip disability and muscle strength negatively.